Analysis on Product Quality of Semi Refined Carrageenan using Six Sigma and Cost of Poor Quality - Bahri, Syamsul; Rahmadani, Fachriah Nur; Darmawan, Armin (Department of Agro-industrial Technology, University of Brawijaya, 2020)
AbstractThe study aimed to minimize defective products to improve the production process quality of PT BI by identifying the most types of defects, calculating Defect per Million Opportunities (DPMO) value, suggesting the quality improvement of the Semi Refined Carrageenan (SRC) production process, and calculating Cost of Poor Quality (COPQ) value. The methods used in this research were Six Sigma and the COPQ. The priority improvement based on the Pareto chart was moisture defects with the percentage of damage of 36.9%. The Sigma level of the production process of PT BI was 3.42 with a defect rate of 27,429 DPMO. The analysis on the cause and effect diagram showed that factors affected the occurrence of defective products were error in reading on moisture content, diverse raw material, the wrong method of mixing raw materials prior to production process, and the lack of inspectors of production process. The most influential-dominant factor was the obsolete machine which causes error in reading on moisture content. The company can take preventive and corrective actions to suppress defective products and improve product quality. Based on the calculation of the COPQ, the costs that must be incurred by the company due to defective products was IDR 1,007,690,694.Keywords: Cost of Poor Quality (COPQ), quality control, seaweed, Six Sigma AbstrakPenelitian ini bertujuan untuk meminimalkan jumlah produk cacat sehingga meningkatkan kualitas proses produksi PT BI dengan mengidentifikasi jenis cacat terbanyak, menghitung nilai Defect per Million Opportunities (DPMO), menyarankan perbaikan kualitas proses produksi Semi Refined Carragenan (SRC) serta menghitung nilai Cost of Poor Quality (COPQ). Metode yang digunakan adalah Six Sigma dan COPQ. Perbaikan yang diprioritaskan berdasarkan diagram Pareto adalah cacat moisture dengan persentase 36,9%. Tingkat Sigma dari proses produksi PT BI adalah 3,42 dengan tingkat kecacatan 27,429 DPMO. Analisis diagram sebab akibat menunjukkan bahwa faktor-faktor yang memengaruhi terjadinya produk cacat adalah kesalahan pada pembacaan kadar air, keragaman bahan baku, metode pencampuran bahan baku yang salah sebelum proses produksi serta kurangnya pengawas proses produksi. Faktor dominan yang paling berpengaruh adalah mesin usang yang menyebabkan kesalahan pembacaan kadar air. Perusahaan dapat mengambil tindakan preventif dan korektif untuk menekan jumlah produk cacat dan meningkatkan kualitas produk. Berdasarkan perhitungan COPQ, biaya yang harus dikeluarkan perusahaan akibat produk cacat adalah sebesar Rp1.007.690.694.Kata kunci: Cost of Poor Quality (COPQ),, pengendalian kualitas, rumput laut, Six Sigma